Effect of Al and Mo substitution on the structural and hydrogen storage properties of CaNi5 - Chumphongphan, Somwan; Paskevicius, Mark; Sheppard, Drew; Buckley, Craig (Elsevier Ltd, 2013)
A simple mechanical milling and annealing process has been used to synthesize CaNi5-based hydrogen storage alloys. Heat treatment at 800°C under vacuum results in theformation of a crystalline CaNi5 phase. Secondary phases, including Ca2Ni7 and MoeNi, areformed when substituting Mo for Ni. Replacement of Ni by Al or Mo leads to an increase inthe unit cell volume of the CaNi5 phase. The hydrogen storage capacity of all substitutedalloys is reduced and the plateau pressures are lower than those of pure CaNi5. Fairly flatplateau regions are retained for all compositions except the CaNi4.8Mo0.2 compositionwhere a Ca2Ni7 phase is dominant. The incorporation of Mo also causes slow sorptionkinetics for the CaNi4.9Mo0.1 alloy. CaNi4.9Al0.1 maintains its initial hydrogen absorptioncapacity for 20 cycles performed at 85°C but the other substituted alloys lose their capacityrapidly, especially the CaNi4.8Mo0.2 composition.